2015
DOI: 10.4049/jimmunol.1400829
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A, But Not IL-17F, Is Indispensable for Airway Vascular Remodeling Induced by Exaggerated Th17 Cell Responses in Prolonged Ovalbumin-Challenged Mice

Abstract: We previously demonstrated an essential role of Th17 cells in excessive mucous secretion and airway smooth muscle proliferation in a prolonged OVA-challenged C57BL/6 mouse model. However, the impact of Th17 cells in vascular remodeling, another characteristic feature of airway remodeling in asthma, remains elusive. This issue was further investigated in this study. The time-course experiments showed that progressively increasing levels of Th17 cells and IL-17A (not IL-17F) in the lungs of prolonged allergen-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…To investigate whether IL-17A can induce direct tubulogenesis, HUVECs seeded on a coat of matrigel were treated with different concentrations of IL-17A in complete endothelial cell growth medium for 16 hours at 37°C prior to the analysis of tubulogenesis, unlike other methods where endothelial cells are serum starved prior to tubulogenesis assay (26). Our data showed that IL-17A induces tubulogenesis of HUVECs on matrigel in a dose dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate whether IL-17A can induce direct tubulogenesis, HUVECs seeded on a coat of matrigel were treated with different concentrations of IL-17A in complete endothelial cell growth medium for 16 hours at 37°C prior to the analysis of tubulogenesis, unlike other methods where endothelial cells are serum starved prior to tubulogenesis assay (26). Our data showed that IL-17A induces tubulogenesis of HUVECs on matrigel in a dose dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, IL-17A is shown to promote direct endothelial cell tubulogenesis in vitro (26, 40). Here, we also show direct effect of IL-17A in promoting tubulogenesis of HUVECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of asthma, administration of IL-17A results in increased vascular remodelling; in vitro , IL-17A accelerates EPC migration (108). …”
Section: The Eosinophil’s Role In Asthma Pathophysiologymentioning
confidence: 99%
“…sEPS neg exacerbates IL-17 responses within the lung. In order to further assess the ability of sEPS neg to promote IL-17 responses in vivo, we utilized the ovalbumin (OVA) sensitization and respiratory challenge model, as we and others previously evidenced potent T H 17 responses within the lungs of challenged animals (35). Either B. longum 35624 or its isogenic derivative sEPS neg was administered intranasally to examine the influence of these strains on IL-17 responses within the lung.…”
Section: Generation Of An Isogenic Exopolysaccharide-negative Derivatmentioning
confidence: 99%